2002
DOI: 10.1093/annonc/13.s1.107
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of upfront dose‐intensive chemotherapy in children with advanced‐stage Hodgkin's lymphoma: preliminary results from the Children's Cancer Group Study CCG‐59704

Abstract: BEACOPP chemotherapy is feasible and generally well tolerated in children with advanced-stage HL. The absence of reported progressive disease and only one relapse to date is encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 10 publications
0
22
0
4
Order By: Relevance
“…22 A legacy Children's Cancer Group trial has reported excellent early efficacy of response-based BEACOPP. 25 Even those patients whose therapy was modified after achieving CR with 4 BEACOPP (adding 4 ABVD for females or 2 ABVD with low-dose radiation therapy for males) still received procarbazine and were exposed to a higher cumulative doxorubicin dose than early responders treated on P9425.…”
Section: Dose Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…22 A legacy Children's Cancer Group trial has reported excellent early efficacy of response-based BEACOPP. 25 Even those patients whose therapy was modified after achieving CR with 4 BEACOPP (adding 4 ABVD for females or 2 ABVD with low-dose radiation therapy for males) still received procarbazine and were exposed to a higher cumulative doxorubicin dose than early responders treated on P9425.…”
Section: Dose Densitymentioning
confidence: 99%
“…This approach diverges from the traditional "response at the end of chemotherapy" used to determine need for additional chemotherapy 20,27 or radiation therapy 8,[20][21][22]25,27 (Table 6). Dorffel et al assessed response at 8 weeks but only in the lowest-risk population.…”
Section: Early-response-based Therapymentioning
confidence: 99%
“…[1][2][3][4][5] In this age group, even patients with recurring disease have a fair chance of cure using various risk-stratified approaches. 6 Autologous hematopoietic stem cell transplantation (HSCT) is increasingly used as salvage therapy also in children 7,8 with poor risk features, although the 2 randomized studies demonstrating superior event-free survival (EFS) and progression-free survival (PFS) after high-dose therapy (HDT) and HSCT included only adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…The use of BEACOPP causes acute toxic effects on bone marrow and also there is a higher late toxicity, with the risk of secondary leukemia, infertility, and heart and lung toxicity. (14) The treatment of advanced stage HL is still under discussion, with ABVD with or without MOPP still used in many countries. (15) The DH-II-90 protocol recommends the use of low-dose involved-field radiotherapy for early-stage HL and extendedfield radiotherapy for stage IV patients and those with B symptoms.…”
Section: Discussionmentioning
confidence: 99%